THE IMPACT STRENGTH AND CORROSION RATE OF THE GTAW WELDING TECHNIQUE ON AA5083 MATERIAL - Dhanang Suryo Prayogo; Sugiarto Sugiarto; Putu Hadi Setyarini (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The 5xx series of Aluminium has strong corrosion resistance, excellent weldability, and good cold workability and also medium strength. This series is being utilized extensively in marine building applications for the construction of Oil tankers, pressure vessels, offshore, ships and other vessels. The purpose of this study is to verify and to ascertain how the welding process affects the corrosion rate and impact strength of 5083 Aluminium. In this experiment, four AA 5083 specimens were warmed to chosen variations of 50°C, 100°C, 150°C, 200°C, and 250°C. The amount of energy absorbed during the fracture process was then determined by subjecting the welding results to a Charpy impact test with varying loads. The best specimen was tested for corrosion rate using the Corrosion Tester 3-Electrode device after comparing impact toughness. According to the study's findings, the specimen with a 250°C preheating step had the maximum impact toughness (0.415) and corrosion rate (0.11353 mmPy).